Implementasi Kaidah Mā Ḥurrimasaddan li al-Żarī’ah Ubīḥa li al-Maṣlaḥah al-Rājiḥah pada Tawaf Ifāḍah bagi Wanita Haid - Muttazimah Muttazimah; Munira Munira; Wilda Reni; Muhamad Saddam Nurdin (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2023)
This research aims to find out and understand the rules of mā ḥurrima saddan li al-żarī'ah ubīḥa li al-maṣlaḥah al-rājiḥah and their implementation in the tawaf ifāḍah of Hajj for menstruating women. This researcher used a type of library research using a normative and conceptual approach. The results of the research found that: first, the rules of mā ḥurrima saddan li al-żarī'ah ubīḥa li al-maṣlaḥah al-rājiḥah (something that is forbidden because of the saddan proposition li al-żarī'ah, then it becomes permissible if there is great benefit). What is forbidden to refuse rather than damage is not all that is absolutely permitted for the benefit or greater good, but it is mandatory to pay attention to the level of the benefit and its fulfillment because the greater benefit is permitted. Second, the prohibition of menstruating women from performing tawaf ifāḍah is saddan li al-żarī'ah that menstruating women are not allowed to pass through or linger in the mosque. However, based on the rules of mā ḥurrima saddan li al-żarī'ah ubīḥa li al-maṣlaḥah al-rājiḥah, contemporary ulama provide special space for the permissibility of tawaf ifāḍah for menstruating women when performing the Hajj. This is by looking at the advantages and disadvantages that the opportunity to perform the Hajj nowadays is not an easy thing, both in terms of time, energy, funds, and opportunities for each person in carrying out the Hajj pilgrimage. It is hoped that the research implications will become a reference, literature or consideration, as well as become a positive reference and information for society in general.